Students’ Difficulties in Reducing Adjective Clauses into Participial Phrases - Witri Oktavia; Noviani Noviani (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2022)
Clause and phrase construction is one of the essential components needs to be mastered by English students in order to support their writing. However, this is the problem that students still encounter. The purposes of this study are to figure out students’ difficulties and the causes of the difficulties in reducing adjective clauses into participial phrases. 30 students were selected using cluster random sampling technique from a population of 162 second-year English Department students at Universitas Negeri Padang. Data gained from questionnaire were analyzed using quantitative approach and descriptive method. The findings demonstrate that understanding adjective clauses (68.8%), using pronouns (64.6%), and constructing verbs (62.8%) are three aspects students found the most problematic. In addition, using relative pronouns is a bit challenging for them (46.6%). It was also found out that these difficulties are significantly influenced by the instructional method utilized (80%), students’ motivation (66.3%), their educational background (65.8%), and learning strategies (63.1%). Indeed, family environment (54.6%) has a fair impact on it as well.